Export induced qualification needs - Maier, Tobias [Verfasser]; Mönnig, Anke [Verfasser]; Zika, Gerd [Verfasser] (My University, 2013)
"Foreign markets determine success and failure of those industries that have become reliant on foreign demand, impair the demand for employment and invoke changes in occupational fields and qualification requirements. This paper aims to disclose the direct and indirect influence of major trading partners on Germany's production, employment, and qualification needs. It projects the effects by using the dynamic macro-econometric input-output model INFORGE. Industrialized economies are the most important determinants for employment in the manufacturing industries. Businessrelated services are highly indirectly affected. The growth impact of industrialized nations is declining while BRICS nations are gaining momentum. A shift towards higher qualification needs can be observed." (Authors' abstract, IAB-Doku)
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; S 6 Berufsbereiche; G 2.1.1 Ökonomie / Märkte; T 3 Forschungsmethoden; Arbeitskräftenachfrage; Projektion; Berufsfeld; Qualifikationsniveau; Modellierung; Input-Output-Analyse; Welthandel